2017
DOI: 10.1097/jom.0000000000001145
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Body Mass on Physical Fitness Test Performance in Male Firefighter Applicants

Abstract: Lighter subjects had a small advantage in endurance-oriented tests while higher mass appeared to improve performance slightly in strength-oriented tests. However, mass explained only 4% to 19% of the variance in performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 25 publications
2
28
0
1
Order By: Relevance
“…The YMCA bench press test requires individuals to successfully move an 80lb barbell, which may favor individuals with more mass. These findings support previous research which has found that firefighters who are considered overweight or obese have diminished health, generally possessed lower levels of fitness, and perform more poorly on physically demanding tasks when compared to their healthy/normal weight counterparts [1][2][3][4]8,13,[26][27][28][29][30].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The YMCA bench press test requires individuals to successfully move an 80lb barbell, which may favor individuals with more mass. These findings support previous research which has found that firefighters who are considered overweight or obese have diminished health, generally possessed lower levels of fitness, and perform more poorly on physically demanding tasks when compared to their healthy/normal weight counterparts [1][2][3][4]8,13,[26][27][28][29][30].…”
Section: Discussionsupporting
confidence: 89%
“…Such analysis allows researchers to determine if certain aspects of fitness impacted firefighter ability more than others. For all regressions, Age and BMI, while not significantly correlated to firefighting ability in this sample, were retained as predictors due to previous evidence suggesting their inverse impact on exertion task ability [2]. Given previous literature highlighting the importance of cardiovascular fitness in firefighters [8][9][10][11][12], estimated VO 2max was entered at the second level, followed by muscular endurance.…”
Section: Data Processing and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent research suggests that these notions are greatly influenced by the exact nature of load carriage; the dimensions and relative mass of load, whether the individual is working against gravity or horizontally, as well as how the load isdistributed on the body 8,10 .As such, researchinto the interaction between performance on these complex job-related tasks and easilymeasuredindices of body mass or compositioncould be valuable. When combined with routinely conducted fitness assessments, these measures may be effectivedeterminants of firefighting performancebuthave not been investigated in UK firefighters.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by our data exhibitinga trend for a body mass bias, such that heavier individuals tended to perform the FFST slower (R=0.276; R 2 =0.08, p=0.02; data not shown), despite the test containing some load carriage.Performance in load carriage tasks can vary based on the dimensions of the mass carried, its distribution on/around the body and the mechanical nature and direction of movement8 . Recent evidence examining firefighting tasks has suggested that lighter individuals may be advantaged in movements where the body must be supported and heavier individuals advantaged when exerting force against high absolute external loads10 .Since this study was not designed to specifically examine load carriage, and the loads carried varied at different stages of the FFST, the precise impacts of individual masses carried cannot be easily discerned and is unfortunately beyond the scope of this paper.However, aside from external load carriage,our data suggestpart of the variance in task performance is likely a product of the contribution of fat mass to total body mass, rather than body mass per se, where high fat mass is commensurate with poorer firefighting task performance.This would explain why, in isolation, relative VO 2 max(i.e. normalised to body mass) appears to predict performance more effectively thanVO 2 maxwith no body mass correction.…”
mentioning
confidence: 98%